Learning-by-doing in a highly skilled profession when stakes are high: Evidence from advanced cancer surgery - Daniel Avdic; Petter Lundborg; Johan Vikström (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2014)
Although learning-by-doing is believed to be an important source of productivity growth, there is limited evidence that production volume affects productivity in a causal sense. We document evidence of learning-by-doing in a highly skilled profession where stakes are high; advanced cancer surgery. For this purpose, we introduce a novel instrument that exploits the closure and opening of entire cancer clinics which have given rise to sharp and exogenous changes in the cancer surgical volumes at Swedish public sector hospitals. Using detailed register data on more than 100,000 episodes of advanced cancer surgery, our results suggest positive effects of surgery volumes on survival. In addition, we provide evidence on the mechanisms through which these improvements occur. We also show that the results are not driven by changes in patient composition or by other changes at the hospital level.
Keywords: I11; I12; I18; L11; 330; hospital volume; learning-by-doing; cancer surgery; survival; causal effect